Approaching Self-Translation in Latin American Indigenous Literatures. The Mapuche Bilingual Poetry of Elicura Chihuailaf and Liliana Ancalao - Stocco, Melisa Soledad (2017)
Approaching self-translation in Latin American Indigenous literatures. The Mapuche bilingual poetry of Elicura Chihuailaf and Liliana Ancalao.